Nutritional aspects of bone health: Not only a matter of vitamin D - Maria Giulia Tinti; Angelo De Cata; Vincenzo Carnevale (Verduci Editore, 2019)
In every stage of life an adequate intake of several micro- and macro-nutrients can favorably affect bone health. In pre-adult life an adequate consumption of such nutrients is essential to build peak bone mass. Later in life, a correct nutrition has a role in maintaining skeletal mass and blunt menopause- and age-related bone loss. The main involved nutrients are calcium, phosphate, vitamin D and proteins. Recent data also stress the relevance of flavonoids and other micro-nutrients. The skeletal availability of single nutritional factors also relies on their reciprocal proportion in diet composition. An adequate nutrition plays a relevant role in the maintenance of bone health throughout life, but it should not be regarded as a treatment for osteoporosis.